Uncommon Pathogen, Lactobacillus, Causing Infective Endocarditis: Case Report and Review - Muhannad Antoun; Yousef Hattab; Fadi-Al Akhrass; Leigh Danielle Hamilton (Case Reports in Infectious Diseases)
Lactobacillus is not a common pathogen; however, it can contribute to opportunistic infections such as infective endocarditis (IE). Nonetheless, it has been reported as case reports in correlation with increased probiotic use, dental caries, and intravenous drug abuse.